Imidazolium‐Substituted Polythiophenes as Efficient Electron Transport Materials Improving Photovoltaic Performance. Issue 9 (19th April 2013) - Kesters, Jurgen; Ghoos, Toon; Penxten, Huguette; Drijkoningen, Jeroen; Vangerven, Tim; Lyons, Dani M.; Verreet, Bregt; Aernouts, Tom; Lutsen, Laurence; Vanderzande, Dirk; Manca, Jean; Maes, Wouter
Abstract In the field of polymer solar cells, improving photovoltaic performance has been the main driver over the past decade. To achieve high power conversion efficiencies, a plethora of new photoactive donor polymers and fullerene derivatives have been developed and blended together in bulk heterojunction active layers. Simultaneously, further optimization of the device architecture is also of major importance. In this respect, we report on the use of specific types of electron transport layers to boost the inherent I–V properties of polymer solar cell devices, resulting in a considerable gain in overall photovoltaic output. Imidazolium‐substituted polythiophenes are introduced as appealing electron transport materials, outperforming the currently available analogous conjugated polyelectrolytes, mainly by an increase in short‐circuit current. The molecular weight of the ionic polythiophenes has been identified as a crucial parameter influencing performance.